Tax credit for support of university-community partnerships in low-income urban school districts - Patel, Krishna (Frontiers in Education, 2024)
Tying public school funding to property taxes has prevented low-income school districts in the United States from garnering adequate financial and social resources. As a result of this regressive funding system, millions of children find themselves trapped in underfunded schools and neighborhoods that perpetuate intergenerational trauma, tenuous employment, poor health, and poverty. However, in many underserved neighborhoods, including in cities like Philadelphia and Chicago, where poverty rates have been as high as 25% and 40%, respectively, many of the most under-resourced schools border or are adjacent to are characterized by their proximity to wealthy universities. 1